Innovating at Marketing and Distributing Nutritious Foods at the Base of the Pyramid (BoP): Insights from 2SCALE, the Largest Incubator for Inclusive Agribusiness in Africa - Dijk, N. van; Velde, N. van der; Macharia, J.; Pipim, K.N.; Shimeles, H. (Springer, 2021)
Toward Sustainable Clusters in Agribusiness through Learning in Entrepreneurship (2SCALE) is the largest incubator for inclusive agribusiness in Africa. Part of this program supports agribusinesses in developing nutritious products that specifically target base of the pyramid (BoP) consumers in local markets. This product development process is complemented with marketing and distribution strategies to ensure these products reach BoP consumers. In an effort to build sustainable and scalable business cases, all strategies are first tested and implemented in short-term pilots. The lessons learned during the implementation of these pilots are presented in this chapter.The goal of this chapter is to showcase the approach, results, and lessons learned while implementing pilots. Under the 2SCALE program, more than 20 agribusinesses have developed new nutritious products and have run marketing and distribution pilots. The lessons derived from this experience can be useful for both agribusinesses themselves and incubating programs.The first section of this chapter highlights the opportunity at the BoP and the rationale behind implementing pilots, including the importance of BoP-specific marketing and distribution strategies. The second one runs through the approach and stages of developing and implementing pilots. This section is followed by an overview of tools and strategies being used in pilot development, whereas the final two sections explain lessons learned and the next steps.